Models of Financing of Natural Monopolies: Budget, Corporate and Project Financing - Sergey N. Silvestrov; Nikolay V. Kuznetsov; Gleb L. Podvoisky; Natalia E. Kotova (Финансы: теория и практика)
Subject. To ensure sustainable economic development of the country, it is necessary that natural (infrastructure) monopolies develop at a faster pace than other sectors of the economy. The state historically played a major role in financing the infrastructure facilities building, however, in the current tense economic situation a trend is to reduce government spending. In these conditions, for natural monopolies, evaluation and selection of the most effective sources of financing their investment activities become of special importance.Goals. Comparative analysis of typical models of financing of natural monopolies — budgetary, corporative and project financing. Identifying their advantages and disadvantages, and identify areas of the most appropriate and effective application.Methodology. The researching is based on a dialectical approach. The researching used systemic, comparative and institutional approaches.Results. Each of the considered models of financing has its advantages and disadvantages, and also is characterized by its specificity of use. For short-term investment projects, as well as renovation projects for existing infrastructure, it is advisable to implement a corporative financing model. Budgetary financing is applicable for projects with a long payback period and projects with conditionally “negative return on investments” (projects with very long payback period). The model of “project financing” is most effective for the implementation of large-scale projects with medium or long-term payback.Conclusions. It is shown that, in the current economic conditions, the implementation of most of the infrastructure tasks included in the strategy of Russia’s economic development can be achieved mainly through the use of project financing. However, its progress in Russia is hindered by the underdevelopment of the legislative base.